ENHANCING ENHANCING STUDENTS' LEARNING INTEREST: THE ROLE OF TEACHER'S TEACHING STYLE AND PARENTAL SUPPORT AT SD NEGERI WADUNGASRI WARU SIDOARJO - safitri, shinta maulidia; Didit Darmawan (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Abstract : This study aims to identify the impact of teachers' teaching styles, parental support, and self-confidence on students' interest in learning. This study focuses on the effect of teacher teaching style, parental support, and self-confidence on student interest in learning at SD Negeri Wadungasri, Waru, Sidoarjo. This research is quantitative research. By involving 103 respondents as a research sample, the sampling technique used was a census. The data collection method used a questionnaire, and data analysis was carried out through a statistical approach. The results showed that the teacher's teaching style, parental support, and self-confidence had a significant effect on student interest in learning at SD Negeri Wadungasri, Waru, Sidoarjo. The findings make an important contribution to the understanding of the factors that influence students' interest in learning at the primary school level. Teachers' teaching style, persistence of parental support, and students' level of self-confidence have a meaningful role in shaping and maintaining students' interest in learning in an educational environment. Keywords: Learning Interest; Teaching Style; Parental Support; Self-Confidence; Teachers; Students